FENOMENA ABORSI DAN HAK HIDUP ANAK DALAM PERSPEKTIF ISLAM - Diana, Ilfi Nur (EGALITA, 2007)
Abortion is very where today, even the womwn who has husband or rich family do it by various reasons. Abortion is a mistreatment and a criminal to the mankind. Al-Quran respect so much to human right which is given by Allah to the mankind, including having right to live. That’s why having right to live for children must be protected as early as possible, taking soul of the children either before or after being born is high level of prohibition in Islam, even many different opinions, one of them is it’s allowed to be done before the trob is found.